Does Financial Literacy Influence Houswife Intention To Use The Islamic Financing? With Trust As A Moderating Variable - Annisa Nur Salam; Siti Nur Azizah (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This study aims to analyze the effect financial literacy on the houswife intention to use islamic financing with trust as a moderating variable. Methodology: This study involved 358 housewife respondent in 32 Indonesian provinces. The model used was based on the theory of reasoned action development with the partial least squares structural equation modeling as the data processing tool. Research Findings : Housewives' financial literacy influences mothers' intentions to use Islamic bank financing products. Originality: Although numerous studies have concentrated on financial literacy and the use of sharia financing, the behaviour of houswife and the high number of housewife loans to informal institutions concern academics and practitioners. This research can highlight the importance of financial literacy for housewives can avoid applying for loans to informal institutions, so sharia financing can be a suitable alternative. Research limitation and implication: The study discovered that financial literacy with variabel ability, attitude and knowledge affect the intention of houswife to use the Islamic financing. Meanwhile, the trust variable failed to moderate the housewife's ability to use Islamic financing. The trust variable was not successful in moderating the attitude and knowledge of the housewife to use Islamic financing. Meanwhile the trust variable significantly moderates the attitude towards the financing variable with a significance